1997
DOI: 10.1128/jvi.71.9.6697-6705.1997
|View full text |Cite
|
Sign up to set email alerts
|

Repeated emergence of epidemic/epizootic Venezuelan equine encephalitis from a single genotype of enzootic subtype ID virus

Abstract: Venezuelan equine encephalitis (VEE) epidemics and equine epizootics occurred periodically in the Americas from the 1920s until the early 1970s, when the causative viruses, subtypes IAB and IC, were postulated to have become extinct. Recent outbreaks in Columbia and Venezuela have renewed interest in the source of epidemic/epizootic viruses and their mechanism of interepizootic maintenance. We performed phylogenetic analyses of VEE virus isolates spanning the entire temporal and geographic range of strains ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
36
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(47 citation statements)
references
References 42 publications
10
36
0
1
Order By: Relevance
“…Even without this correction, the monophyly of VEE virus subtype I and subtype II strains (excluding subtype IF 78V-3531 virus) and the monophyly of subtype III strains are absolute, regardless of the region analyzed or algorithm used (Powers et al, 1997;Kinney et al, 1998). The phylogenetic clustering of EVE virus with subtype IAB, IC, and ID strains has been previously noted (Powers et al, 1997;Kinney et al, 1998), as has the clustering of 78V-3531 virus with subtype VI AG80-663 virus. A reclassification of VEE virus subtype IF and subtype II strains has been proposed , to which the complete nucleotide sequences reported here provide further support.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Even without this correction, the monophyly of VEE virus subtype I and subtype II strains (excluding subtype IF 78V-3531 virus) and the monophyly of subtype III strains are absolute, regardless of the region analyzed or algorithm used (Powers et al, 1997;Kinney et al, 1998). The phylogenetic clustering of EVE virus with subtype IAB, IC, and ID strains has been previously noted (Powers et al, 1997;Kinney et al, 1998), as has the clustering of 78V-3531 virus with subtype VI AG80-663 virus. A reclassification of VEE virus subtype IF and subtype II strains has been proposed , to which the complete nucleotide sequences reported here provide further support.…”
Section: Discussionmentioning
confidence: 90%
“…Many of the experiments which helped define functions or functional residues for these proteins were prompted by or directed by sequence comparisons (Ahlquist et al, 1985;Hardy and Strauss, 1989;Rozanov et al, 1992;Strauss et al, 1992;Wang et al, 1996;Ahola et al, 1997;Shirako and Strauss, 1998), and support for additional proposed nsP properties relies on shared identity with viral or nonviral proteins of known function (Gorbalenya et al, 1988;Rikkonen et al, 1994). Potential VEE virus epizootic residues have been identified in structural proteins by sequence comparison (Powers et al, 1997;Kinney et al, 1998;Oberste et al, 1998). Functional attributes of 'epizootic nsPs' must be defined for similar comparisons in the nonstructural region to have meaning (LaStarza et al, 1994a;Oberste et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18][19][20] For example, within the VEE virus ID serologic variant, isolates from Colombia, Venezuela, and the Amazon basin, from Panama, and from the Pacific coast of Colombia and Ecuador are antigenically and/or genetically distinct from one another. 11,15,16,19,21 Phylogenetic analyses indicated that IE strains were monophyletic relative to other VEE virus subtypes, but that there were at least three distinct lineages (genotypes) within the IE subtype ( Figure 1). The Gulf/Caribbean coast genotype consisted of viruses isolated in Belize and eastern Mexico (Tabasco and Veracruz states) from 1963 to 1991.…”
Section: Resultsmentioning
confidence: 99%
“…nigripalpus, two abundant, widespread mammalophilic species, may explain why outbreaks of EVEV have not occurred in South Florida. Previous studies 43,44 indicate that epidemic/epizootic VEEV emerge from subtype ID strains, the closest relatives of EVEV. Such emergence events arise when combinations of mutations that alter equine virulence and/or mosquito infectivity occur in concert with appropriate ecological conditions.…”
Section: Discussionmentioning
confidence: 99%